2020
DOI: 10.3390/biology10010006
|View full text |Cite
|
Sign up to set email alerts
|

Adipose and Muscle Cell Co-Culture System: A Novel In Vitro Tool to Mimic the In Vivo Cellular Environment

Abstract: A co-culture system allows researchers to investigate the complex interactions between two cell types under various environments, such as those that promote differentiation and growth as well as those that mimic healthy and diseased states, in vitro. In this paper, we review the most common co-culture systems for myocytes and adipocytes. The in vitro techniques mimic the in vivo environment and are used to investigate the causal relationships between different cell lines. Here, we briefly discuss mono-culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 75 publications
0
15
0
Order By: Relevance
“…Fat and muscle cells both secrete various factors that can impact one another's proliferation, differentiation, and metabolism. [ 425 ] This relationship is complex. For example, it has been reported that co‐culture with fat cells both promotes [ 426 ] and suppresses [ 427 ] differentiation of muscle cells.…”
Section: Engineering Biological and Structural Complexitymentioning
confidence: 99%
“…Fat and muscle cells both secrete various factors that can impact one another's proliferation, differentiation, and metabolism. [ 425 ] This relationship is complex. For example, it has been reported that co‐culture with fat cells both promotes [ 426 ] and suppresses [ 427 ] differentiation of muscle cells.…”
Section: Engineering Biological and Structural Complexitymentioning
confidence: 99%
“…In biological research, the co-culture system closely resembles in vivo cellular physiology and interactions. Co-culture techniques have been used to explore the relationship between adipose and muscle tissue in a variety of settings, including pharmacological responses, secretory factor production and effect, cell growth, and development [ 83 ]. The discovery of adipo-myokine secretory factors, which are generated by adipocytes and myocytes to drive differentiation and proliferation, was made possible by interactions between co-cultured myoblasts and adipocytes [ 83 ].…”
Section: Co-culture Of Adipose and Muscle Tissuementioning
confidence: 99%
“…Co-culture techniques have been used to explore the relationship between adipose and muscle tissue in a variety of settings, including pharmacological responses, secretory factor production and effect, cell growth, and development [ 83 ]. The discovery of adipo-myokine secretory factors, which are generated by adipocytes and myocytes to drive differentiation and proliferation, was made possible by interactions between co-cultured myoblasts and adipocytes [ 83 ]. In the co-culture method, differentiation myoblasts control pre-adipocyte differentiation, whereas pre-adipocytes stimulate adipogenic gene expression in MSCs co-cultured with pre-adipocytes.…”
Section: Co-culture Of Adipose and Muscle Tissuementioning
confidence: 99%
“…Different in vitro co-culture systems have been developed to study cell-cell interactions, and these systems can be generally classied into two categories: indirect co-culture (i.e., co-culture without cell contact) and direct co-culture (i.e., co-culture with cell contact). [16][17][18][19][20] In indirect co-culture systems, different types of cells are physically segregated (e.g., cells cultured in different devices or different chambers of the same device 21 ), whereas cell-cell communication is through the shared culture medium (e.g., via the permeable membrane in a culture device or channels in a microuidic device 22,23 ) or conditioned medium harvested from the other types of cells. 24 This type of co-culture method is commonly used due to its high reproducibility and commercially available cell culture devices.…”
Section: Introductionmentioning
confidence: 99%